THE IMPORTANCE OF TEACHER PEDAGOGICAL COMPETENCE IN IMPROVING THE QUALITY OF EDUCATION - Feruzabonu Ravshanova (Modern American Journals, 2025)
This article highlights the significance of teacher pedagogical competence in the process of improving the quality of education. As one of the key factors determining educational quality, the teacher’s professional knowledge, skills, competencies, innovative approaches, and personal attributes are examined. The concept of pedagogical competence is broadly interpreted, and its components — methodological, communicative, psychological, ethical, and technological competencies — are analyzed. Furthermore, modern approaches to developing teacher competence are emphasized, including the effective use of information and communication technologies, reflection, and self-assessment mechanisms. The article evaluates the development of pedagogical competence as a fundamental condition for enhancing the quality of education and draws on national and international experiences as examples. Finally, practical recommendations and suggestions aimed at improving educational quality are presented. This article may be useful for educators, researchers, and specialists interested in advancing education quality.
Keywords: Quality of education, pedagogical competence, teacher qualification, professional development, innovative pedagogy, methodological competence, modern education, self-development, teacher activity.